Determinants of Breast Milk Donation and Use among Postpartum Women at a City Hospital in Nairobi, Kenya - Jane Wanjiku Kanyi; Alice Sipiyian Lakati; Theresa Odero (Journal of Epidemiology and Public Health, 2025)
Background: The World Health Organization advocates donor human milk as a superior substitute for newborns unable to obtain their mother’s milk. Calls have been made to scale up human milk banks to provide infants without access to mother’s milk safe donor human milk. This research sought to assess determinants of breast milk donation and the use of donor human milk among postpartum women.Subjects and Method: This cross-sectional study was conducted in May 2023 at a government hospital with human milk banking facilities. A consecutive sampling technique was used to recruit a sample of 370 postpartum women admitted to the postnatal wards. A pretested interview-based questionnaire was used to obtain participants’ sociodemographic data, breastfeeding history, peri-natal characteristics, awareness of human milk banking, and other general factors that might influence acceptance to donate breast milk and the use of donated human milk. Data was analyzed using R-4.3.0 software and descriptive statistics were done for all variables. Further inferential statistics including the Chi-Square test and multivariate logistics regression were computed with a significance level set at α=0.050.Results: The mother’s willingness to donate breast milk and use donor human milk was 78.1% and 70.8% respectively. The respondent’s age (OR=0.42; 95% CI=0.19 to 0.94; p=0.035) was significantly associated with willingness to donate breast milk. Religion (OR=0.27; 95% CI=0.10 to 0.72; p =0.009) and awareness of human milk banking (OR=0.89; 95%CI= 1.07 to 3.36; p= 0.029) were significant predictors of willingness to use donor human milk.Conclusion: Human milk banking awareness was low among the study population; however, mothers are willing to donate and use donated breast milk. Age in years is significantly associated with willingness to donate while religion and awareness of human milk banking are significant predictors of use.